2002
DOI: 10.1536/jhj.43.273
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Na+/H+ Exchanger Isoform 1 (NHE1) in Non-infarcted Myocardium after Acute Myocardial Infarction.

Abstract: SUMMARYAlthough cardiac NHE1 is activated during myocardial ischemia and reperfusion injury, little is known about changes in expression in non-infarcted myocardium after acute myocardial infarction (AMI). The purpose of this study was to examine left ventricular function and region dependent NHE1 expression after myocardial infarction. Therefore, we produced two AMI models in rats, a small infarction model which was continuously ligated at the branches of the left coronary artery, and an extensive infarction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…While the NHE1 mRNA level was strongly upregulated only after acidic SI, this pH dependence was not detected at the protein level, a phenomenon that we currently cannot explain. Similar to our findings, NHE1 mRNA and protein levels were reduced in the noninfarcted part of rat myocardium after myocardial infarction (52), and NHE1 upregulation during reperfusion after I/R was also reported in rat hearts (9,13). In accordance with the lack of detectable caspase-3 activation during SI per se, Western blot analysis did not reveal the presence of NHE1 cleavage products (data not shown); hence, it seems likely that the downregulation of NHE1 protein levels in SI reflects the reduction at the mRNA level.…”
Section: Discussionsupporting
confidence: 92%
“…While the NHE1 mRNA level was strongly upregulated only after acidic SI, this pH dependence was not detected at the protein level, a phenomenon that we currently cannot explain. Similar to our findings, NHE1 mRNA and protein levels were reduced in the noninfarcted part of rat myocardium after myocardial infarction (52), and NHE1 upregulation during reperfusion after I/R was also reported in rat hearts (9,13). In accordance with the lack of detectable caspase-3 activation during SI per se, Western blot analysis did not reveal the presence of NHE1 cleavage products (data not shown); hence, it seems likely that the downregulation of NHE1 protein levels in SI reflects the reduction at the mRNA level.…”
Section: Discussionsupporting
confidence: 92%
“…Another explanation for the negative results of the clinical trials is that the level of NHE may have varied considerably among the participants. Sodium-hydrogen exchanger 1 mRNA has been reported to increase after an ischaemic episode except when the myocardium has been exposed to ischaemic preconditioning (Dyck et al 1995, decreased expression of NHE1 has been observed following myocardial infarction (Shimohama et al 2002), and increased activity with no change in expression has been found in patients with chronic endstage heart failure . In the clinical trials, the subjects were administered treatments following initial symptoms of cardiovascular failure that may have altered the NHE in various ways thereby attenuating the effect of an NHE inhibitor.…”
Section: Sodium-hydrogen Exchangermentioning
confidence: 99%
“…The methods were similar to those previously reported for cardiac muscle of laboratory animals (8,49). Frozen muscle biopsies (ϳ200 mg) were cut into small pieces and homogenized for 30 s in 2 ml of ice cold lysis buffer containing 50 mM Tris ⅐ HCl (pH 7.4), 50 mM EDTA, 150 mM NaCl, 0.1% Triton 100, 1 mg/ml pepstatin, 200 mM phenylmethyl sulfonyl fluoride, and 1 mg/ml leupeptin.…”
Section: Chemical Analysis Of Muscle Biopsiesmentioning
confidence: 99%